A molecular phylogeny of Garuleum (Calenduleae, Asteraceae) in southern Africa - Jackson, Mariëtte; van Zyl, Juanita; Frylinck, Magdil; Joubert, Lize (Phytotaxa, 2024)
We present the first complete molecular phylogeny for the genus Garuleum (Calenduleae, Asteraceae), which is endemic to South Africa and Namibia. To investigate the phylogenetic relationships, sequence data from plastid trnL-trnF and nuclear ITS were analysed with Parsimony and Bayesian Inference approaches. The genus is resolved as monophyletic and G. bipinnatum is shown as the first species to diverge from the group. Four well to moderately supported subclades were identified where the species distribution ranges within a subclade were distinct. The wide distribution of G. bipinnatum was ascribed to its heterocarpic fruit, and the distribution of the genus was possibly influenced by water availability and elevation. These results confirmed the previous molecular work in which some Garuleum species were included.